2003
DOI: 10.1002/ijc.11621
|View full text |Cite
|
Sign up to set email alerts
|

p66Shc protein is upregulated by steroid hormones in hormone‐sensitive cancer cells and in primary prostate carcinomas

Abstract: Members of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
75
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(79 citation statements)
references
References 35 publications
4
75
0
Order By: Relevance
“…To the best of our knowledge, this is the first report that p66Shc-ROS pathway mediates early androgenic cell proliferation in androgen-sensitive prostate cancer cells, which is independent of AR-dependent gene expression, such as PSA. Data obtained from this study, thus, provide a molecular explanation for the clinical observations on increased p66Shc and ROS production in archival prostate cancer specimens (Lee et al, 2004a;Lim et al, 2005). In parallel, increased levels of H 2 O 2 -producing enzymes, such as Nox1 and SOD, are also noticed in prostate cancer specimens (Kuruma et al, 2005;Lim et al, 2005).…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…To the best of our knowledge, this is the first report that p66Shc-ROS pathway mediates early androgenic cell proliferation in androgen-sensitive prostate cancer cells, which is independent of AR-dependent gene expression, such as PSA. Data obtained from this study, thus, provide a molecular explanation for the clinical observations on increased p66Shc and ROS production in archival prostate cancer specimens (Lee et al, 2004a;Lim et al, 2005). In parallel, increased levels of H 2 O 2 -producing enzymes, such as Nox1 and SOD, are also noticed in prostate cancer specimens (Kuruma et al, 2005;Lim et al, 2005).…”
Section: Discussionsupporting
confidence: 63%
“…p66Shc regulates DHT-induced proliferation in prostate cancer cells Previous studies indicated that p66Shc, which increases intracellular ROS levels, is elevated in DHT-treated prostate cancer cells (Lee et al, 2004a; Figure 3a). Furthermore, semiquantitative analyses of the blots indicated a significantly higher level of p66Shc protein from 8 h of DHT treatment (Po0.05) (Supplementary Figure 1) prior to increase in ROS production (16 h), as indicated by an dichlorofluorescein diacetate (DCF-DA) fluorescence (Figure 3b), and the stimulation of cell proliferation, as indicated by the increase in Cyclin D1 level (24 h) (Figure 3a), the percentage of cells at S-phase (24 h) ( Figure 3c) and cell number (48 h) (Figure 3d).…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations